The quest for knowledge transfer efficacy: blended teaching, online and in-class, with consideration of learning typologies for non-traditional and traditional students - Van Doorn, Judy R.; Van Doorn, John D. (Frontiers in Psychology, 2014)
The pedagogical paradigm shift in higher education to 24-h learning environments composed of teaching delivery methods of online courses, blended/hybrid formats, and face-to-face (f2f) classes is increasing access to global, lifelong learning. Online degrees have been offered at 62.4% of 2800 colleges and universities. Students can now design flexible, life-balanced course schedules. Higher knowledge transfer rates may exist with blended course formats with online quizzes and valuable class time set for Socratic, quality discussions and creative team presentations. Research indicates that younger, traditional students exhibit heightened performance goal orientations and prefer entertaining professors who are funny, whereas non-traditional students exhibit mastery profiles and prefer courses taught by flexible, yet organized, professors. A 5-year study found that amongst 51,000 students taking both f2f and online courses, higher online failure rates occurred. Competing life roles for non-traditional students and reading and writing needs for at-risk students suggest that performance may be better if programs are started in f2f courses. Models on effective knowledge transfer consider the planning process, delivery methods, and workplace application, but a gap exists for identifying the diversity of learner needs. Higher education enrollments are being compromised with lower online retention rates. Therefore, the main purpose of this review is to delineate disparate learning styles and present a typology for the learning needs of traditional and non-traditional students. Secondly, psychology as a science may need more rigorous curriculum markers like mapping APA guidelines to knowledge objectives, critical assignments, and student learning outcomes (SLOs) (e.g., online rubric assessments for scoring APA style critical thinking essays on selected New York Times books). Efficacious knowledge transfer to diverse, 21st century students should be the Academy's focus.